Presence of endothelial progenitor cells, distinct from mature endothelial cells, within human CD146+ blood cells - Delorme, Bruno; Basire, Agnès; Gentile, Carla; Sabatier, Florence; Monsonis, Frédéric; Desouches, Christophe; Blot-Chabaud, Marcel; Uzan, Georges; Sampol, José; Dignat-George, Françoise (Thrombosis and Haemostasis, 2005)
CD146 is an adhesion molecule present on endothelial cells throughout the vascular tree. CD146 is also expressed by circulating endothelial cells (CECs) widely considered to be mature endothelial cells detached from injured vessels. The discovery of circulating endothelial progenitor cells (EPCs) originating from bone marrow prompted us to investigate whether CD146 circulating cells could also contains EPCs. We tested this hypothesis using an approach combining elimination of CECs by an adhesion step, followed by immunomagnetic sorting of remaining CD146+ cells from the non adherent fraction of cord blood mononuclear cells. When cultured under endothelial-promoting conditions, these cells differentiated as late outgrowth endothelial colonies: they grew as a cobblestone monolayer, were uniformly positive for endothelial markers and did not express leukocyte antigens. They highly proliferated and were expanded in long-term culture without alterations of their phenotypic and functional properties (DiI-ac-LDL uptake, wound repair, capillary-like network formation, and TNFα response). Moreover, these cells colonized a Matrigel plug in immunodeficient mice (NOD/SCID). Finally, using 4-color flow cytometry analysis of purified CD34+ cells, we clearly discriminated, CD146+ EPCs (CD146+ CD34+ CD45+ CD133+ or CD117+), and CD146+ CECs (CD146+ CD34+, CD45− CD133− or CD117−), both in cord and adult peripheral blood. The relative proportions of the two CD146+ subsets varied in patients with myocardial infarction as compared to healthy subjects. Our study establishes that, beside CECs, CD146+ circulating cells contain a subpopulation of EPCs with potential use in proangiogenic therapy. In addition, the dual measurement of CD146+ CECs and CD146+ EPCs offers a promising tool for monitoring vascular injury/regeneration processes in clinical situations.
Keywords: CD146; angiogenesis; myocardial infarction; circulating endothelial cells; progenitor endothelial cells